Breakthrough victories: How can a loser ever win?. Issue 1 (2nd January 2017) - Gaffney, Paul
Abstract: The domain of sport provides opportunity for development and growth, which is often incremental but can be marked by significant breakthroughs. Using Aristotle's virtue ethic as a model, this paper explores the challenge of overcoming new obstacles, sometimes reversing bad habits, in the athletic domain. Breakthrough victories in sport are achievements that both reward persistent effort and open new horizons in the pursuit of excellence. They are significant because they seem to hold out a promise for future performance, now that some barrier has been passed. Breakthrough victories are often among the most important and rewarding moments in an athletic career.